The Influence of Software Engineering Education on Developing Teamwork Skills in Both Genders - Maria Cecilia Bastarrica; Jocelyn Simmonds (IEEE Access, 2025)
Teamwork is recognized as a highly valuable skill for any software engineer. In computer science programs it is typically developed through project-based courses, though these courses often do not adopt a gender-oriented approach. Women are underrepresented in the software industry, and there is limited knowledge about their teamwork competencies. While some studies compare teamwork skills between men and women, few have explored the impact of education on the development of this skill, particularly in relation to different aspects of teamwork. By comparing teamwork quality between genders at different program levels, we intend to gain valuable insights about students’ initial teamwork skills and the effect of software engineering education over time. To do this, we have carried out an empirical study of two project-based software engineering courses in our Computer Science and Engineering program: an introductory software engineering course and a capstone course. In each case we evaluate different aspects of teamwork by applying the same peer assessment instrument along 13 semesters. Our study revealed no significant gender-based disparities within the courses under study, indicating that such differences are absent both in students’ initial abilities and final competencies. What we did observe, however, is that women’s teamwork assessments are more homogeneous over time than the men’s, where we see significant improvements in Attitude, Motivation, Coordination and Communication between courses. Our results lead us to believe that, it takes men longer to reach the same capacity for working in teams than women, but in the end, students of both genders reach similar teamwork capabilities in all teamwork quality dimensions. Therefore, women have just as much potential to excel as software engineers as men, especially when it comes to teamwork.